Negative life events and psychological distress and life satisfaction in U.S. college students: The moderating effects of optimism, hope, and gratitude - Abdi Gungor; Mark E. Young; Stephen A. Sivo (Journal of Pedagogical Research, 2021)
Negative life events are unpleasant, stressful, and uncontrollable experiences found to be risk factors for increased psychological distress and decreased life satisfaction in college students. In addition, distress and life satisfaction are closely related to college students' quality of life and academic performance. Conversely, positive psychological states have been hypothesized to buffer the effects of negative life events. Data from 738 college students in the U.S. were analyzed to examine the moderating effects of three positive psychological variables on negative life events: optimism, hope, and gratitude.  The results showed that negative life events positively predicted distress and negatively predicted life satisfaction. The results also revealed that optimism, hope, and gratitude moderated the effects of negative life events. The authors conclude that the evidence supports positive psychology interventions in college counseling to combat the effects of negative life events through the positive psychological states of optimism, hope, and gratitude. The specific clinical implications for practicing counselors and educational settings are suggested.